2011
DOI: 10.1242/dev.057646
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt9b signaling balances progenitor cell expansion and differentiation during kidney development

Abstract: SUMMARYThe mammalian kidney is composed of thousands of individual epithelial tubules known as nephrons. Deficits in nephron number are associated with myriad diseases ranging from complete organ failure to congenital hypertension. A balance between differentiation and maintenance of a mesenchymal progenitor cell population determines the final number of nephrons. How this balance is struck is poorly understood. Previous studies have suggested that Wnt9b/-catenin signaling induced differentiation (mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
324
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(339 citation statements)
references
References 35 publications
(69 reference statements)
13
324
1
1
Order By: Relevance
“…12 Uninduced nephron progenitors express "stemness" genes such as Six2 but are also poised to undergo mesenchymeto-epithelium transition in response to inductive Wnt signaling emanating from the adjacent UB. [13][14][15] In this regard, Six2 interacts and cooperates with Lef/Tcf factors and β-catenin to initiate expression of nephrogenic genes such as Wnt4, Lhx1, Pax8, and Fgf8. We recently examined the chromatin landscape in MM cell lines using ChIP-Seq and reported that whereas H3K4me3 peaks predominantly decorate metabolic genes, H3K27me3 peaks are highly specific to developmental genes in each cell line.…”
Section: Introductionmentioning
confidence: 99%
“…12 Uninduced nephron progenitors express "stemness" genes such as Six2 but are also poised to undergo mesenchymeto-epithelium transition in response to inductive Wnt signaling emanating from the adjacent UB. [13][14][15] In this regard, Six2 interacts and cooperates with Lef/Tcf factors and β-catenin to initiate expression of nephrogenic genes such as Wnt4, Lhx1, Pax8, and Fgf8. We recently examined the chromatin landscape in MM cell lines using ChIP-Seq and reported that whereas H3K4me3 peaks predominantly decorate metabolic genes, H3K27me3 peaks are highly specific to developmental genes in each cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Release of Wnt9b from the UB branches triggers a ␤-catenindependent morphogenetic program leading to expression of Wnt4, Fgf8, and Pax8 and transition of ventrally located MM cells to epithelial nephron progenitors (pretubular aggregates and renal vesicles) (23,24). Wnt9b signaling cooperates with Six2, a transcription factor expressed exclusively in the dorsal metanephric cap region to maintain the proliferation or selfrenewal of pluripotent MM cells (25)(26)(27). Subsequently, the Lim homeodomain transcription factor, Lhx1 (also known as Lim-1), a downstream target of Wnt4/Fgf8 signaling, mediates further maturation to comma-and S-shaped bodies (28 -30).…”
mentioning
confidence: 99%
“…21 Although the nephron progenitor population is initially present and specified correctly in Wnt9b mutants, it shows a very low proliferation rate relative to wildtype. 22 Treatment of isolated mesenchyme with Wnt9b leads to expansion and maintenance of the nephron progenitors alongside the MET, suggesting that Wnt9b also promotes proliferation. This could be a direct role for Wnt9b on the progenitors or an indirect role resulting from Wnt9b's ability to induce renal vesicles.…”
Section: Met and Proliferationmentioning
confidence: 99%